MAKASSAR'S PUBLIC HEALTH PERCEPTION IN THE TRADITION OF CONSUMPTION OF LALAPAN: CULTURAL PERSPECTIVES AND HEALTH COMMUNICATION - Haliza, Siti Nurul; Alimuddin, Alimuddin; Qalby, Moch. Noer Alim (Journal of Entrepreneur, Business and Management, 2025)
Culture and communication are two entities that form each other, where culture is learned through the process of communication, while communication reflects the cultural value system that lives in society. In this context, culture is not only understood as a habit, but as a social construct that is inherited across generations through family interactions, formal education, and informal learning such as folklore, local beliefs, and everyday practices. In the people of Makassar, the tradition of consuming lalapan is one of the expressions of eating culture that is full of health meaning, because this practice is not only related to the fulfillment of biological needs, but also represents local knowledge about the balance of the body and nature. The view of health in the local tradition is built through collective experience and disseminated through interpersonal communication between generations, especially in the family and community environment. These values are learned from an early age through the example of parents, verbal advice, and social reinforcement in daily life, thus forming the perception that lalapan is a symbol of a natural healthy lifestyle. This study aims to describe how the people of Makassar construct the meaning of health through the tradition of consumption of lalapan in the perspective of culture and health communication. The qualitative approach is used to explore people's subjective understanding of the concept of health, the process of inheriting the value of eating culture, and the role of communication in maintaining these practices. Through in-depth interviews and literature studies, this study found that Makassar's public health views are formed through a multi-layered social learning process, including informal learning, formal education, and internalization of cultural values through local narratives and collective customs. Thus, the tradition of consuming lalapan not only functions as a food practice, but also as a medium of health communication that strengthens cultural identity while maintaining the sustainability of local values in the face of modern social changes.Keywords: Culture, Health Communication, Makassar Community, Lalapan Tradition, Health Views